Lies and epiphanies composers and their inspiration from Wagner to Berg - Walton, Chris 1963- (University of Rochester Press, 2014)
Lies and Epiphanies offers case studies of "inspiration" in five composers -- Richard Wagner, Gustav Mahler, Wilhelm FurtwaÌngler, Richard Strauss, and Alban Berg. Their own tales of their epiphanies played a determining role in the reception history of their works: the finale of Mahler's Second Symphony was supposedly born of a "lightning bolt" of inspiration at the funeral of Hans von BuÌlow, while Alban Berg's Violin Concerto was purportedly his direct response to the tragic early death of Alma Mahler's daughter. Chris Walton looks behind these tales to explore instead the composer's dual role as author and self-commentator, laying bare the fissures and inconsistencieswithin these artists' testimonies and revealing how the putatively extrarational world of creative inspiration intersects with the highly rational world of money and politics. As Walton points out, the composer often imposes on the audience an interpretation of a work and its genesis that is as superficial as the score itself is not. This study seeks to show why
Title from publisher's bibliographic system (viewed on 10 Feb 2023)
Richard Wagner's dynastic dreams -- Gustav Mahler's resurrection and the apostolic succession -- Of forked tongues and angels : Alban Berg's violin concerto -- Wilhelm Furtwängler and the return of the muse -- Here comes the sunset : the late and the last works of Richard Strauss -- Postlude : the telephone call
Keywords: Furtwängler, Wilhelm -- 1886-1954; Strauss, Richard -- 1864-1949; Wagner, Richard -- 1813-1883; Berg, Alban -- 1885-1935; Mahler, Gustav -- 1860-1911; Composition (Music); Composers; Inspiration; Creation (Literary, artistic, etc.); Kreativität; Komponist; Offenbarung; Komposition -- Musik